Utilization of Groundwater, Spring, and the Surface Water for Drinking Water Service for the People of Surakarta - Team PDAM Surakarta (Forum Geografi, 2000)
Case study: utilizing the groundwater, water resources, and surface of water to supply the drinking water for the inhabitants is Surakarta. Of the early target at 75%, the supply of drinking water for the inhabitants in Surakarta only achieves 44%. Because of this, the Regional Drinking Water ompany (PDAM) of Surakarta made a decision to: 1) utilize the debit of water production by making a deep well at a capacity of 30 liters a second for a short term, and on the basis of the study of water resource for Surakarta, for a long term; 2) minimize the water loss from 37% to 22%; and 3) fix and extend the network of distribution. In a comprehensive consideration, there are two alternatives to add the debit of water production water: 1) utilazing the water supply at 50 liters a second from Mount Lawu. However, this is not sufficient to supply the drinking water at a capacity of 200 liters a second; and 2) utilizing the water from Colo Dam with the IPA system. This can hopefully fulfill a lack of drinking water supply at 200 liters a second. However, utilizing the natural water from the groundwater must be continued to decrease PDAM’s supply.